The relationship of compliance with immediate and delayed suggestibility and types of resistant behavioral responses in children aged 10–15 years - Gudjonsson, Gisli; Giostra, Valeria; Maiorano, Tiziana; Vagni, Monia (Frontiers in Psychology, 2024)
This study examined the relationship of compliance with immediate and delayed suggestibility and types of resistant behavioral responses (RBRs) in 454 children (10–15 years) using the Gudjonsson Suggestibility Scale (GSS 2) and a slightly adapted version of the Gudjonsson Compliance Scale (GCS). The GCS was found to have satisfactory internal consistency with this age group. Immediate suggestibility and delayed suggestibility were significantly correlated (small effect size). Compliance was most strongly correlated with Yield 1 (large effect size) and Yield 2 (medium effect size) and only modestly with Shift and delayed suggestibility (both small effect size). Of both theoretical and practical importance was the finding that out of the three resistant behavioral responses (RBRs) where misleading questions were not yielded to, ‘direct explanation’ and ‘no answers’ were the only salient predictors of compliance. ‘Do not know’ answers were found to have the weakest association with compliance. The current findings help better understand the complex relationship of compliance with immediate suggestibility (i.e., Yield and Shift), RBRs, and delayed suggestibility in children. The findings have important implications for future studies as well as interview practice.